Use of a Novel Device in Reconstructive Venous Surgery: Preliminary Results - Camilli, Daniele; Platone, Alessandro; Ruggeri, Massimo; Furgiuele, Sergio (International Journal of Angiology, 2020)
Evaluation of the outcomes of OSES (oval-shaped external support), a novel device for external valvuloplasty of the great saphenous vein (GSV) for the conservative treatment of superficial venous insufficiency. Between 2012 and 2015, 30 patients underwent external valvuloplasty of the GSV for a total of 32 limbs. Patients were subjected to clinical and instrumental follow-up by a half-year ultrasound for a minimum of 36 months. The main endpoints were the recurrence of varicose disease, persistent or recurrent venous reflux, and venous thrombosis. Varicose recurrence was verified in six limbs on 32 (18.75%). Four limbs (12.5%) presented a recurrence of the reflux even in the absence of varicose veins. Two limbs (6.25%) underwent saphenectomy after the valvuloplasty intervention at 12 and 18 months, respectively, because of the presence of saphenofemoral reflux and varicose recurrences. No case of venous thrombosis of the saphenous trunk was observed. The external valvuloplasty of the GSV is a well-known technique that used to treat the superficial venous insufficiency. The newly introduced OSES device seems to show better midterm results, due to a better alignment of the valve flaps. In our experience, the use of this device gives better long-term results and allowed to extend the indication to patients with saphenic diameters that were considered not eligible for repair. In conclusion, although our data needs further confirmation, OSES device might represents a new interesting opportunity for reconstructive venous surgery.
Keywords: valvuloplasty; varicose veins; vein reflux; venous insufficiency; vessel repair; vein patch; venous ulcer